Penguatan Personal Branding untuk Pengembangan Karir Manajemen - Kariza, Cesy Iola (Dianmas Bhakti: Jurnal Pengabdian pada Masyarakat, 2025)
Digitalization has transformed the way individuals build their professional identity, where personal branding has become a crucial factor in enhancing career competitiveness. However, students of the Management Study Program, Faculty of Economics and Business, Universitas Panca Bhakti still lack a comprehensive understanding of this concept, which may lead to challenges in entering the workforce. This Community Service Program (PkM) aimed to provide relevant knowledge aligned with career development in management. The method involved material preparation, coordination with partners, and the implementation of an interactive seminar combined with self-reflection sessions. The solution offered was to equip students with knowledge of the fundamentals of personal branding, strategies for building it in the digital era, and reflective practices to help them identify their unique values and competencies. The results revealed an improvement in students’ understanding of the importance of personal branding, active participation in discussions, and new awareness of presenting an authentic and consistent professional image. Therefore, this program successfully bridged theory and practice while also providing recommendations for students and institutions to continue developing advanced initiatives to strengthen personal branding.